Dizem que os cães vêem coisas: o transitar dos manuscritos - Melo, Terezinha Alves (2009)
This work is in focus on the collection of the manuscripts linked to the short stories “ The Letter” and “The Dog”, both belonging to the book They say the dogs see things, 1st and 2nd editions, in order to undestand the itinerary of the writting of the author from Ceara, Moreira Campos. For this purpose, we have based this work on the fundamentals of Genetic Criticism theory, a new current of research in the field of the arts, that is aimed at demonstrating the process of the artistic creation, making use of inferencies about the used procedures starting from the marks left by the author in the way of his creation. This study is structured on: presentation, five chapters, conclusion, attacheds and bibliographic references. In the first chapter, we described the origin of AMEC of UFC, because it is the source of our research, giving priority to Moreira Campos’ collection. We classified his documents and related his first results. In the second chapter, we presented a synthesis about Moreira Campos’ life and work: Personal and literary specifities. In the third chapter, we gave na account of trajectory of Genetic Criticism, her precursors, her origin in France and in Brazil, based on Almuth Gresillon’s view, the methodology idealized by Pierre- Marc de Biasi and readings enriched by brazilian researchers and foreign’s works, always refered in footnote. In the fourth chapter, we analyzed the corpus: its complexibility and particularity. We gave details of our work object, in other words, of the collection of integratings documents in the genetic dossiers of the short stories “The Letter” and “The Dog”, attached for us until the present moment: describing the origin of each version (support, writting instrument, phisical conditions). In the fifth chapter, we specified the criteria to the analyzis of our study object; compared the versions of each short stories, its various stages of elaboration, including those constants in editions revised by the author; indicated the variants between the compared versions, analyzing them in order to verify the procedures used by Moreira Camposin his production; and we developed hypotheses about his process of creation, starting from the marks of his campaingn about the text. In conclusion, we commented on our inferencies about the wings of Moreira Campos’ writting based on stylistic informations of the author and on theorical presupposings of Genetic Criticism. We perceived some recurring pratices of writting and rewritting that can allow unique characteristics of strategies used by the author in his literary creation, like adaptation of texts to news prototypes of language, the approuch of the fictional language and the search for the synthesis.